The antihyperglycemic activity of bruguiera gymnorrhiza roots extract in stz-induced diabetic mice - Intan Zulaikha Md Zainin; Julenah Ag Nuddin; Ruzaidi Azli Mohd Mokhtar (Penerbit UMS, 2024)
Mangrove plants are believed to possess a wide range of bioactive compounds due to their ability to thrive in harsh conditions enduring high salinity, low air humidity and high temperature. Bruguiera gymnorrhiza is one of the mangrove species that is commonly found in Sabah and its root has been discovered to have antidiabetic activity. However, previous investigations focused solely on ethanolic extract of Bruguiera gymnorrhiza root (BGR). Thus, this study aimed to assess antihyperglycemic activity of BGR methanolic extract in various fractions (aqueous, butanol, chloroform) using streptozocin-induced diabetic mice as an experimental model. The diabetic mice were administered different fractions of BGR extract at dose of 250 mg/kg with metformin (200 mg/kg) serves as standard drug. Blood glucose levels were measured on day 0th, 7th and 14th following the oral administration of BGR fractions in a fasting state mice. After 14 days treatment period, the results showed that the aqueous fraction of BGR extract significantly reduced the blood glucose levels in diabetic mice compared to other BGR fractions. The significant antihyperglycemic effect observed in aqueous fraction of BGR extract strongly indicates the presence of major potent antidiabetic components for decreasing the elevated blood glucose levels in diabetic mice.